(untitled) (Horn of Africa Journal of Social Science, 2024)
Polio campaigns are routinely conducted in Somalia and the ministry of health engages radios, TVs, mounted car announcements, and community mobilizers. Purpose: The assignment was initiated in order to assess the effectiveness of polio mass media campaigns with respect to outreach to targeted audiences and understanding of the messages of the various media, channels, and contents. Design/methodology: A quantitative method has been used for the data collection; The study heavily relies on primary data collection from the field. Visited houses were randomly selected in targeted districts. Findings The findings of this study indicate that, 7 out of 10 people surveyed cited that mass media as their source of information about polio campaigns. Also the study found Misconceptions, misinformation, fear as well as intricate tribal and cultural norms are challenges facing polio campaign in Benadir region. Research limitations/implications. This study only emphasized Benadir region polio cmapaign; thus, the findings of the present study may not be applicable to other countries. Originality/value: Limited studies have been conducted to investigate the impact of Polio post-campaign communication in Benadir region Somalia